1994
DOI: 10.1111/j.1432-2277.1994.tb01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Nodular regenerative hyperplasia: a controversial indication for orthotopic liver transplantation

Abstract: Nodular regenerative hyperplasia of the liver is an uncommon cause of portal hypertension. Patients with nodular regenerative hyperplasia have signs and symptoms of portal hypertension, without evidence of hepatocellular failure or encephalopathy. We report the case of a 44-year-old woman with recurrent esophageal bleeding and refractory ascites who had a history of hemosiderosis, hepatitis C, and chronic renal allograft rejection. Our preoperative diagnosis was cirrhotic end-stage liver disease and end-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In our patients, as in previously reported patients, OLT was decided on because of the rapidly progressive, life-threatening complications of portal hypertension and liver disease and the inef cacy of surgical or radiological porto-systemic shunting, as attempted in three of our patients. In two of our patients, combined liver and renal transplantation was performed because of associated severe renal failure; this association has been reported in two previous cases (10,14). In our series, the delay between the initial diagnosis and OLT was short: 4.5 years (range 3-10).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In our patients, as in previously reported patients, OLT was decided on because of the rapidly progressive, life-threatening complications of portal hypertension and liver disease and the inef cacy of surgical or radiological porto-systemic shunting, as attempted in three of our patients. In two of our patients, combined liver and renal transplantation was performed because of associated severe renal failure; this association has been reported in two previous cases (10,14). In our series, the delay between the initial diagnosis and OLT was short: 4.5 years (range 3-10).…”
Section: Discussionmentioning
confidence: 72%
“…The histopathological diagnosis was NRHL in eight patients (7)(8)(9)(10)(11)14), ISC in two (12,13) and partial nodular transformation of the liver in one (14). In our patients, as in previously reported patients, OLT was decided on because of the rapidly progressive, life-threatening complications of portal hypertension and liver disease and the inef cacy of surgical or radiological porto-systemic shunting, as attempted in three of our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Clinically, NH may be without signs or symptoms, may be associated with biochemical abnormalities in the absence of physical signs, and may also be the cause of profound portal hypertension. 21,22,26,28,32,35,55,65 There is a long list of associated conditions, 22,55,66 and the presence of portal hypertension in a patient with one of these disorders should suggest the possibility of NH.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients the complications of portal hypertension are sufficiently severe to warrant liver transplantation. [12][13][14][15][16][17] In a recent study, Saigal et al 7 have demonstrated that small fraction of patients with NCPF (INCPH) (∼5%) do develop ascites, jaundice, and hepatic encephalopathy making it difficult to differentiate it from cirrhosis of liver. The diagnosis of NCPF (INCPH) was missed prior to the liver transplant and had a pre-transplant diagnosis of cirrhosis of unknown or some known etiology.…”
Section: Spectrum Of Idiopathic Noncirrhotic Portal Hypertensionmentioning
confidence: 99%